2009
DOI: 10.1016/j.poetic.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to music exploration in a digital age

Abstract: This paper looks at the largely unexplored terrain of how young people find music that is new to them in an environment with an unprecedented number of possibilities. Digital media has changed not only how artists create and distribute content, but also how listeners find and access new material. The new options exist in the context of older traditions such as using one's social networks or traditional media to find content. Based on original data with a sample of college students, we find that while students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 47 publications
5
64
0
12
Order By: Relevance
“…Technological advances impact culture, and this is something to remember when looking at more recent generations (Holbrook, 2000;Lefsetz, 2014;Tepper & Hargittai, 2009 and when trying to party with others. All while on the other side, we have the other relative half of the portion of this group that listens to music all day (Bahanovich & Collopy, 2009;Gewen, 2008;Tepper & Hargittai, 2009).…”
Section: The Millennial Experience and Reasons For That Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…Technological advances impact culture, and this is something to remember when looking at more recent generations (Holbrook, 2000;Lefsetz, 2014;Tepper & Hargittai, 2009 and when trying to party with others. All while on the other side, we have the other relative half of the portion of this group that listens to music all day (Bahanovich & Collopy, 2009;Gewen, 2008;Tepper & Hargittai, 2009).…”
Section: The Millennial Experience and Reasons For That Experiencementioning
confidence: 99%
“…All while on the other side, we have the other relative half of the portion of this group that listens to music all day (Bahanovich & Collopy, 2009;Gewen, 2008;Tepper & Hargittai, 2009). Scholars in this field have yet to integrate a holistic understanding of this population and their music consumption values (Brown, 2008), but there is data on their music consumption behavior.…”
Section: The Millennial Experience and Reasons For That Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…These range from the loss of an aesthetic discourse to the situation in which search algorithms send audiences to music from only their preferred styles. However, in a study of how college students discover new music, Tepper and Hargittai (2009) found that while online resources matter, social networks and traditional media continue to play an important role. In sum, more research is needed before we can draw conclusions about the full impact of new technology on either cultural producers or consumers.…”
mentioning
confidence: 99%